Effect of Carica papaya (paw-paw) aqueous leaf extract on the growth, haematological parameters and the liver enzymes of Clarias gariepinus juveniles - Nkiruka Francisca Oparaku; Maureen Ukwueze; Chigozie Godwin Nwosu; Felix Andong; Daniel Echiude; Elijah Okwuonu; Ngozi Ezenwaji (Aquaculture Reports, 2024)
It is common practice to use herbs to supplement for fish feed and as a way to trap fish during fishing expeditions. The use of these plant materials causes more harm than good in aquaculture species because of lack of knowledge of the side effects. The study was to find acute toxicity of the lethal dose (LD50) of Carica papaya leaf extract on Clarias gariepinus juveniles, hematological parameters, weight changes, liver enzymes. A total number of 200 C. gariepinus juveniles were used for the study. Juveniles were grouped into 5 groups for acute toxicity with different extract concentrations; 290.95 mg/l, 529.00 mg/l, 767.05 mg/l, 1005.10 mg/l, and 1243.15 mg/l. Based on the result of acute toxicity tests, assessment of sub-acute toxicity test was made, using different extract concentration; 290.00 mg/l, 502.50 mg/l, 714.15 mg/l and 925.75 mg/l. Administration of extract lasted for 28 days behavioural changes were observed in the experimental animals at the 96 h static bioassay. Weight were observed, specific growth rate was the lowest in 925.75 mg/l and the control. Hematological assay showed changes in the packed cell volume (PCV), red blood cell count (RBC), haemoglobin concentration (Hb), mean corpuscular volume (MCV), and mean corpuscular haemoglobin (MCH) as they were significantly increased in comparison to the control. Mean corpuscular haemoglobin concentration (MCHC) showed no response except on day 7 when it declined significantly in fish exposed to 290.0 mg/l of extract. The white blood cell differentials and liver enzymes-alanine aminotransferase activity (ALT), aspartate aminotransferase activity (AST) and alkaline phosphatase (ALP) were unaffected. The increase in red blood cell may be indicative that leaf extract of Carica papaya may have anti-anaemic properties. The absence of changes in the white blood cell and liver function enzymes, may be indicative that C. papaya leaf extract has no toxic effect on the juveniles.